PERMAINAN MINI TENIS UNTUK PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SISWA SEKOLAH DASAR - Alim, Abdul (Jurnal Pendidikan Jasmani Indonesia, 2009)
Essentially, physical education is an educational process that utilize physical activity to bring out a holistic changes in an individual quality in terms of physical and emotional. As an educator, teacher ought to know students characteristic and implementing appropriate teaching methods. Moreover, to considering the elementary school age children, an impact of education can also start from the learners need. In order to know the need of the elementary school, it is necessity to identify from their developmental tasks. Thus, the understanding toward the learners characteristic and developmental tasks are the starting point to determine elementary education purposes and to establish proper time for giving education in accordance with the children need. Keywords: Mini Tennis, Physical Education, Instructional, Elementary.